2008
DOI: 10.1021/bi801461d
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Redox-Active Chlorophylls in the Secondary Electron-Transfer Pathways of Oxygen-Evolving Photosystem II

Abstract: Photosystem II (PS II) is unique among photosynthetic reaction centers in having secondary electron donors that compete with the primary electron donors for reduction of P 680 + . We have characterized the photooxidation and dark decay of the redox-active accessory chlorophylls (Chl) and β-carotenes (Car) in oxygen-evolving PS II core complexes by near-IR absorbance and EPR spectroscopies at cryogenic temperatures. In contrast to previous results for Mn-depleted PS II, multiple near-IR absorption bands are res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…It is possible that other pigments further from the reaction centre may undergo oxidation due to further oxidation of side-path components. Reports exist in the literature of multiple chlorophylls and carotenoids undergoing slow bleachings with prolonged illumination [104]. Such oxidations, should they occur under physiologically relevant conditions, may be considered as oxidative leaks.…”
Section: Side Path Futile Cycle and Oxidative Leaks In Psiimentioning
confidence: 99%
“…It is possible that other pigments further from the reaction centre may undergo oxidation due to further oxidation of side-path components. Reports exist in the literature of multiple chlorophylls and carotenoids undergoing slow bleachings with prolonged illumination [104]. Such oxidations, should they occur under physiologically relevant conditions, may be considered as oxidative leaks.…”
Section: Side Path Futile Cycle and Oxidative Leaks In Psiimentioning
confidence: 99%
“…[1][2][3][4][5] An important aim in the development of such molecular circuits is to create chemically stable molecular scaffolds possessing well-defined configurations that can be systematically varied to control the magnitude of the conductance output.P ossessing such capability is vital to mimic some aspects of conventional electronics, such as the design of resis-tors with precise resistance values and limited tolerance. [24] We have previously developed synthetic routes for these naturally occurring molecules with exquisite control over their geometry and chemical stability, and we have recently demonstrated their utility as single-molecule wires. [6][7][8][9][10][11][12] This, in turn, confers ag reat degree of freedom to tune the conductance magnitude of organic molecules.…”
mentioning
confidence: 99%
“…[24] We have previously developed synthetic routes for these naturally occurring molecules with exquisite control over their geometry and chemical stability, and we have recently demonstrated their utility as single-molecule wires. Their conjugated nature and planarc onformation of the alkene chain maximizes the overlap of the p-orbitals, openingc hannels for electron transport at large distances.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that there are at least two redox-active carotenoids (Car ∙+ ) in PSII based on the shift of the Car ∙ + near-IR peak over a range of illumination temperatures and the wavelength-dependant decay rate of the Car ∙ + absorbance (Tracewell and Brudvig 2003 ; Telfer et al 2003 ). There are as many as 5 redox-active Chl (Chl ∙+ ) (Tracewell and Brudvig 2008 ; Telfer et al 1990 ), with one ligated to D1-His 118 (Stewart et al 1998 ). However, there are 11 Car and 35 Chl per PSII, as seen in Fig.…”
Section: Introductionmentioning
confidence: 99%